"Apocrine Hidrocystoma and Cystadenoma"–like Tumor of the Digits or Toes: A Potential Diagnostic Pitfall of Digital Papillary Adenocarcinoma. (March 2016) - Molina-Ruiz, Ana-María; Llamas-Velasco, Mar; Rütten, Arno; Cerroni, Lorenzo; Requena, Luis
Abstract : Digital papillary carcinoma (DPC) is a rare, underreported, and often misdiagnosed malignant tumor of the sweat glands. It is often located on the digits and toes and most commonly occurs in male individuals in their fifties to seventies. Because of lack of pain, slow growth, and an inconspicuous appearance, clinical diagnosis is often missed or delayed. In contrast, apocrine hidrocystoma (AH) is a cystic adenoma that arises from the apocrine secretory coil, and it is extremely rare for AHs to develop on the digits. We report 7 cases of DPC, including clinical course, histopathologic and immunohistochemical findings, and therapeutic approach in which the initial histopathologic diagnosis in all cases was AH or cystadenoma. However, complete excision of the neoplasms led to a final diagnosis of DPC. After an adequate treatment, no recurrence or metastasis was found in any of the cases described. All the cases studied showed similar histopathologic and immunohistochemical findings. The initial incisional biopsy showed large unilocular or multilocular cystic spaces situated within the dermis, lined by a double layer of epithelial cells with tiny papillary structures. No cellular atypia, necrosis, or pleomorphism was observed. However, complete excision revealed neoplastic lesions involving the dermis and/or subcutis, with an infiltrative pattern and papillary projections into luminal spaces. Immunoperoxidase studies showed positivity for CK7, S-100 protein, CEA, p63, smooth muscle actin, and calponin. DPC is a rare but life-threatening malignancy, therefore it is important to be able to identify such a lesion both clinically and histopathologically, treat it, and monitor the patient for the tumor's potential recurrence and metastasis. Pathologists and dermatopathologists should be aware that a histopathologic diagnosis of AH or cystadenoma on the fingers and toes should be established with caution, because probably those lesions represent the superficial and cystic component of an underlying DPC, and a wider excision should be performed.